Mechanism of Acupuncture in Treating Stroke Patients with Foot-drop - Li, Xinyan; Feng, Weixing (Journal of Contemporary Medical Practice, 2024)
Post-stroke foot drop leads to impaired walking ability and seriously affects the physical and mental health of patients and their families. This review discusses the effects of acupuncture on promoting the recovery of upper motor neurons, inhibiting the excitability of spinal motor neurons, regulating spasm-related transmitters, and regulating the balance of muscle tone between active and antagonist. This review discusses the effects of acupuncture on promoting the recovery of upper motor neurons, inhibiting the excitability of spinal motor neurons, regulating spasm-related transmitters, and regulating the balance of muscle tone between active and antagonistic muscles, with the aim of exploring the possible pathways of acupuncture in the treatment of post-stroke foot drop and providing a direction for the study of the mechanism of acupuncture in the treatment of post-stroke foot drop. It is important for the modernization of Chinese medicine treatment methods.